Chemically driven superstructural ordering leading to giant unit cells in unconventional clathrates Cs8Zn18Sb28 and Cs8Cd18Sb28. Issue 37 (16th September 2020) - Owens-Baird, Bryan; Yox, Philip; Lee, Shannon; Carroll, Xian B.; Grass Wang, Suyin; Chen, Yu-Sheng; Lebedev, Oleg I.; Kovnir, Kirill
Abstract : Giant clathrate supercell driven by ordering of Zn/Sb bonding in the framework and Cs-guest vacancies is found in unconventional clathrate Cs8 Zn18 Sb28 . Abstract : The unconventional clathrates, Cs8 Zn18 Sb28 and Cs8 Cd18 Sb28, were synthesized and reinvestigated. These clathrates exhibit unique and extensive superstructural ordering of the clathrate-I structure that was not initially reported. Cs8 Cd18 Sb28 orders in the Ia 3̄ d space group (no. 230) with 8 times larger volume of the unit cell in which most framework atoms segregate into distinct Cd and Sb sites. The structure of Cs8 Zn18 Sb28 is much more complicated, with an 18-fold increase of unit cell volume accompanied by significant reduction of symmetry down to P 2 (no. 3) monoclinic space group. This structure was revealed by a combination of synchrotron X-ray diffraction and electron microscopy techniques. A full solid solution, Cs8 Zn18− x Cd x Sb28, was also synthesized and characterized. These compounds follow Vegard's law in regard to their primitive unit cell sizes and melting points. Variable temperature in situ synchrotron powder X-ray diffraction was used to study the formation and melting of Cs8 Zn18 Sb28 . Due to the heavy elements comprising clathrate framework and the complex structural ordering, the synthesized clathrates exhibit ultralow thermal conductivities, all under 0.8 W m −1 K −1 at room temperature. Cs8 Zn9 Cd9 Sb28 and Cs8 Zn4.5 Cd13.5 Sb28 both have total thermal conductivities of 0.49 W m −1 K −1 at room temperature, among the lowest reported for any clathrate. Cs8 Zn18 Sb28 has typical p-type semiconducting charge transport properties, while the remaining clathrates show unusual n–p transitions or sharp increases of thermopower at low temperatures. Estimations of the bandgaps as activation energy for resistivity dependences show an anomalous widening and then shrinking of the bandgap with increasing Cd-content.